Propuesta urbano arquitectónica de un terminal de buses interprovincial para la ciudad de Ibarra - Portilla Vallejo, Marco Antonio (2024)
The objective of this work is to develop an urban-architectural proposal for an interprovincial bus terminal for the city of Ibarra. This proposal seeks to contribute to the mobility and urban development of the city. To achieve this, an investigation is carried out using a methodology that involves the use of different techniques and tools to understand the current situation of the terminal. These techniques include conducting surveys, interviews, field visits and photographic surveys. In chapters one, two, three, four and five of the project, topics related to theories, conceptualization, diagnosis and architectural proposal are addressed. Analysis is carried out on land transportation and urban mobility, detailing aspects such as justification, importance, scope, spatial and functional needs. During the development of this project, multiple objectives are established in order to guarantee that the final proposal meets all the immediate and future expectations of this equipment in a satisfactory manner. The objective is to offer an urban and architectural solution that contributes to improving the movement of people and goods in the canton.